Network Dynamics Governed by Lyapunov Functions: From Memory to Classification. Issue 7 (July 2020) - Stern, Merav; Shea-Brown, Eric
Abstract : In 1982, John Hopfield published a neural network model for memory retrieval, a model that became a cornerstone in theoretical neuroscience. In a recent paper, Krotov and Hopfield built on these early studies and showed how a network that incorporates a biologically plausible learning rule governed by a Lyapunov function can effectively perform classification tasks.